Abundance and distribution of microplastics in seawater, sediment, and macroalgae sea grapes Caulerpa racemosa from Semak Daun Island, Jakarta Bay, Indonesia - MUFTI PETALA PATRIA; NOER KHOLIS; DIAN ANGGREINI; FAEIZA BUYONG (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Patria MP, Kholis N, Anggreini D, Buyong F. 2023. Abundance and distribution of microplastics in seawater, sediment, and macroalgae sea grapes Caulerpa racemosa from Semak Daun Island, Jakarta Bay, Indonesia. Biodiversitas 24: 3424-3430. Microplastic pollution in marine ecosystems poses a significant global concern, specifically regarding the security of food derived from the sea. Macroalgae, as a food source from the sea, can be susceptible to contamination by microplastics. This research assessed the abundance and forms of microplastics in macroalgae sea grapes (Caulerpa racemosa (Forssk.) J.Agardh) collected from Semak Daun Island within the Seribu Island National Park. Additionally, the impact of washing and stirring on microplastic abundance was examined in macroalgae. The average number of microplastics and their identification showed that the washed, stirred, and NaOH-treated macroalgae samples contained an average abundance of 3.28±0.31 particles/g, 5.06±0.59 particles/g, and 2.0±0.81 particles/g, respectively. Furthermore, microplastics were detected in seawater and sediment samples, with an average abundance of 8.2±2.19 particles/L and 15,200±4,932 particles/Kg, respectively. Fragmented microplastics were the predominant form in macroalgae, while fibrous microplastics dominated seawater and sediment samples. Significant differences were observed between the washed and stirred samples (p = 0.009), where the stirred sample exhibited a higher reduction percentage. Microplastics in edible macroalgae indicated the potential hazards of exposure and subsequent accumulation in the human body.